New Host Plant Species of Grapevine Virus A Identified with Vector-Mediated Infections - Vončina, Darko (Plant disease, 2024)
Grapevine virus A (GVA) is an economically important virus and a member of the genus Vitivirus (family Betaflexiviridae) that causes a range of symptoms with qualitative and quantitative effects on grape production. Wild and domesticated species of Vitis, including hybrids used as rootstocks, are considered important natural hosts of GVA. Mechanical transmission to some herbaceous plant species, graft transmission, and vector transmission from grape to grape by various mealybugs and soft scale insects have been reported. Under laboratory and greenhouse conditions, this study demonstrates the transmission of GVA from grapes to alternative hosts by the vine mealybug (Planococcus ficus). Results of ELISA, end-point one-step RT-PCR, and real-time RT-PCR, and in some cases electron microscopy and genome sequencing, confirmed successful transmission to three new plant species commonly found in Croatian vineyards: velvetleaf (Abutilon theophrasti), redroot pigweed (Amaranthus retroflexus), and field poppy (Papaver rhoeas), along with Chenopodium murale and the previously known host Nicotiana benthamiana, with variable infection rates. Depending on the host species, symptoms in the form of leaf reddening, yellow spots, reduced growth of lateral shoots, systemic vein clearing, foliar deformation and rugosity, and dwarfism were observed in GVA-infected plants, whereas no symptoms were observed in infected plants of A. theophrasti. Reverse transmission from these new hosts to grapevines by Pl. ficus was not successful. These results confirm four new GVA host species and open new research venues